Mapping of slope instability in steeply sloping basins using the infinite slope approach. - Alfaro Alejo, Roberto (2022)
Areas with a steep slope and with the presence of rain are susceptible to landslides, which in turn can cause other disasters. The objective of this research is to determine the landslide hazard map using deterministic methods, as a case study in the Cuyocuyo river basin, located in the northeast area of the department of Puno, belonging to the Amazon watershed, considered a moderately rainy and steep slopes. The mapping of ground instability is carried out considering landslides as surface translational, controlled by convergence of groundwater flow, using the infinite slope model. The data required to implement the model includes topography, soil properties, and water states that are highly variable in both space and time. The landslide inventory is used as verification at the points of occurrence. As results, for the saturated, semi-saturated and dry soil conditions, the safety factor is between the unstable and very unstable classes, at 42%, 38% and 18% of the basin area, respectively; which is indicative of a landslide-prone area. The information provided by landslide susceptibility maps helps authorities and technicians to adopt hazard reduction strategies for existing and future landslides through prevention, mitigation and evasion.